Assessing Soil Potassium: Basic Principles and New Developments. Issue 2 (7th March 2023) - Leverich Nigon, Leanna; Bruulsema, Tom
Abstract : Potassium (K) is an essential element for crop growth, playing a key role in photosynthesis, protein synthesis, and many other essential functions in the plant. In 2020, 44% of the soils sampled across North America tested below critical in K (meaning applying K fertilizer would result in a crop response). Assessing soils for nutrient availability is an important principle of 4R Nutrient Stewardship. The goal of this article is to provide information on the behavior of K in soils and how it influences the assessment of crop K needs. Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses .